Cassava Wastewater and Solid Waste Leachate as Cyanogenic Substrates for the Growth of Nitrile and Linamarin-Utilizing Bacteria - Ogunyemi, Adewale Kayode; Samuel, Titilola Aderonke; Ilori, Mathew Olusoji; Amund, Olukayode Oladipo (Journal of Tropical Life Science, 2019)
The direct discharge of wastewaters containing cyanogenic compounds poses severe health hazards, hence this study aimed to establish the biodegradative potential of nitrile and linamarin utilizing bacterial strains in the degradation of cyanogens in cassava wastewaters (CWW) and solid waste leachates (SWL). Glutaronitrile-utilizing bacterial strains (Bacillus sp. strain WOD8 KX774193 and Corynebacterium sp. strains WOIS2 KX774194) were isolated from solid waste leachates while linamarin-utilizing bacteria strains (Bacillus pumilus strain WOB3 KX774195 and Bacillus pumilus strain WOB7 KX774196) were isolated from cassava wastewaters. They were identified on the basis of morphological and biochemical characteristics, microscopic and 16S rRNA gene sequencing. Microbial growth assessment coupled with pH changes were performed under aerobic batch conditions. Growth was evaluated at intervals (2 days) by the intensity of turbidity (O.D. 600 nm) in CWW and SWL media. The doubling times of strains WOD8 and WOIS2 when grown on CWW and SWL (without supplementing mineral salts medium) were 12.83 and 10.83 d (specific growth rate, µ: 0.054 and 0.064 d-1) and 20.38 and 17.77 d (µ: 0.034 and 0.039 d-1) respectively. Also, strains WOD8 and WOIS2 grew on supplemented CWW and SWL with doubling times of 10.04 and 9.9 d (µ: 0.069 and 0.070 d-1) and 16.12 and 16.12 d (µ: 0.043 and 0.043 d-1) respectively. Similarly, the doubling times of strains WOB3 and WOB7 when grown on CWW and SWL (without supplementing mineral salts medium) were 8.25 and 7.53 d (µ: 0.084 and 0.092 d-1) and 8.66 and 9.90 d (µ: 0.080 and 0.070 d-1) respectively. Whereas, the same strains had doubling times of 6.30 and 5.78 (µ: 0.11 and 0.12 d-1) and 6.30 and 9.24 (µ: 0.11 and 0.075 d-1) respectively when grown on supplemented CWW and SWL. It would appear that CWW has the highest potential as a natural growth substrate than SWL, and its use for biomass production may contribute to a reduction in the overall environmental impact generated by discarding cyanogenic residues.